Assessing quality and safety of animal feeds. (Rome : Food and Agriculture Organization of the United Nations, 2004)
This publication provides information on the impact of animal feeds on food quality, food safety, and the environment, and thus improves the basis for managing such risks. The book brings together in printed form six reviews from the FAO electronic journal AGRIPPA (available online).
"TC/M/Y5159E/1/12.03/1500"--P. [4] of cover.
Keywords: Feeds -- Quality; Feeds -- Contamination